2018
DOI: 10.1093/molehr/gay006
|View full text |Cite
|
Sign up to set email alerts
|

Leydig cell dysfunction is associated with post-transcriptional deregulation of CYP17A1 in men with Sertoli cell-only syndrome

Abstract: This work was supported by the National Fund for Scientific and Technological Development (FONDECYT) of Chile to A.C. [grant number 1120176]. The authors declare no conflict of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In this regard, it has been shown that murine Leydig cells deficient in SULT1E1 accumulates cholesterol esters and exhibit steroidogenic impairment with low T production as a result of reduced 17α‐hydroxilase and 17–20 lyase (CYP17A1) expression and activity 12 . Recently, we reported that the immunoreaction of CYP17A1 is decreased in Leydig cells of patients with SCOS, low T/LH ratio, and high intratesticular concentration of E2, suggesting a negative effect of E2 over T biosynthesis 40 …”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it has been shown that murine Leydig cells deficient in SULT1E1 accumulates cholesterol esters and exhibit steroidogenic impairment with low T production as a result of reduced 17α‐hydroxilase and 17–20 lyase (CYP17A1) expression and activity 12 . Recently, we reported that the immunoreaction of CYP17A1 is decreased in Leydig cells of patients with SCOS, low T/LH ratio, and high intratesticular concentration of E2, suggesting a negative effect of E2 over T biosynthesis 40 …”
Section: Discussionmentioning
confidence: 99%
“…Representative images were captured for each sample under the same light intensity and exposure time conditions. The mean-to-area ratio of the integrated optical density parameter (mean IOD) for each subject was used as semiquantitative [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“… 35 Further studies utilizing dissection technologies of targeted cells from tissues such as a laser capture microdissection are required to quantitate INSL3 mRNA and peptide accurately at cellular levels. 37 , 38 , 39 …”
Section: Insl3 Structure Expression Receptor and Rolesmentioning
confidence: 99%
“…35 Further studies utilizing dissection technologies of targeted cells from tissues such as a laser capture microdissection are required to quantitate INSL3 mRNA and peptide accurately at cellular levels. [37][38][39] Ferlin et al 40 have suggested a modulating effect of INSL3 on bone metabolism and linking gene mutations of INSL3 receptors with human osteoporosis. They also demonstrated the role of INSL3 and its receptor system in protein turnover, contributing to muscle wasting in male hypogonadism.…”
Section: Expressioningonadsmentioning
confidence: 99%
See 1 more Smart Citation